GP82 Prevalance rates for avoidant restrictive food intake disorder (ARFID) in tertitary feeding clinic in UK. (June 2019) - Spicer, Lucy; Strudwick, Katy; Kelly, Veronica
Abstract : We present the prevalence rates of Avoidant Restrictive Food Intake Disorder (ARFID) in our tertiary feeding service. ARFID is a relatively recent DSM –V diagnostic category that describes children with complex feeding disorders. Previous diagnoses of 'feeding disorders of infancy or early childhood' in the DSM-IV were limited and excluded children who maintained a healthy weight in the context of problematic eating behaviours. According to the DSM V in 2013 ARFID describes those children with an apparent lack of interest in food, food-avoidance based on its sensory characteristics and/or concerns about the aversive consequences of eating due to persistent failure to meet appropriate nutritional and/or energy needs are all symptomatic of ARFID. The prevalence rates of ARFID are currently unknown. In specialist psychiatric and medical settings it is estimated to be between 5–13%. The clinical characteristics of children with complex feeding difficulties are currently poorly described in the literature, making it difficult to identify and plan necessary services. Our service is a tertiary multidisciplinary feeding service that receives on average 250 referrals per annum. Of those referrals, 150 are referred to r the Complex Feeding Clinic and the others are for medical, dysphagia or videofluroscopy clinics. The Complex Feeding Service is formed of a Consultant Paediatrician, Psychologist, Occupational Therapist, Dietictian and Speech and Language Therapist. We accept referrals for children both locally and regionally, on the provision that there is a named local professional to liaise with. Our referral criteria includes children up to 18 years old with complex feeding difficulties which may cause psychosocial or nutritional impairment. Such feeding difficulties may be related to: an underlying ASD diagnosis, a developmental feeding disorder, medical disorder, sensory selectivity and/or anxiety around foods. The children who attend our clinic may be fed by enteral means or have a selective eating pattern (not otherwise stated). We chart the emergence of this diagnosis within our cohort of patients and track its increasing use since it was included in the DSM V in 2013. We also analyse the following characteristics within the cohort of children receiving this diagnosis: gender, age, with/without a diagnosis of ASD or other co morbid neurodevelopmental issues, nutritional adequacy, diet range and fed by enteral means i.e. NG/PEG.